2018
DOI: 10.3390/f9050270
|View full text |Cite
|
Sign up to set email alerts
|

Building Resistance and Resilience: Regeneration Should Not be Left to Chance

Abstract: Contemporary forest planning has tasked managers with developing goals associated with resistance and resilience. In practice, silviculturists use forest structure and tree species composition to characterize goals and desired future conditions, write prescriptions, and monitor outcomes associated with resistance and resilience. Although rarely discussed in the exploding literature relating to forest resistance and resilience, silvicultural regeneration methods are important and underutilized tools to meet the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
4
0
3
Order By: Relevance
“…This is consistent with previous research that suggests that greater tree diversity contributes to lower-severity outbreaks by diluting the abundance of any given host (Connor et al, 2014;Guo et al, 2019;Jactel & Brockerhoff, 2007). Our results thus lend broad support to management strategies that promote resilience through increased tree diversity, which may help reduce stand-scale severity and increase the chances for recovery (Long et al, 2018).…”
Section: Implications For Management and Future Researchsupporting
confidence: 91%
“…This is consistent with previous research that suggests that greater tree diversity contributes to lower-severity outbreaks by diluting the abundance of any given host (Connor et al, 2014;Guo et al, 2019;Jactel & Brockerhoff, 2007). Our results thus lend broad support to management strategies that promote resilience through increased tree diversity, which may help reduce stand-scale severity and increase the chances for recovery (Long et al, 2018).…”
Section: Implications For Management and Future Researchsupporting
confidence: 91%
“…This method is based on the succession theory of tropical natural forests. In line with this theory, the research results of Long et al (2018) showed that the management of Engelmann spruce in Intermountain West used a small group selection cutting system, which is preferred because it mimics the dynamics of the gap phase. Furthermore, some research on gap opening and planting for rehabilitation of degraded natural forests in Indonesia dan Brazil showed that the cultivation of local superior intolerant tree species using gap opening and planting is more costeffective and needs shorter-term investment (Grogan et al, 2013;Schwartz et al, 2017;Elias & Suwarna, 2019).…”
Section: Introductionmentioning
confidence: 82%
“…Two remaining questions for these dry second-growth ponderosa pine forests are: what is the long-term effect of the different treatments on future regeneration [35,36], and what is the optimal minimum spacing between overstory trees, between pole-sized trees, and between sawlog-sized trees for improving restoration prescriptions [37,38]? An assessment of fuel loading, snag life cycles, and soils will be assessed in a future manuscript.…”
Section: Discussionmentioning
confidence: 99%